The nomadic bug: a case report of salmonella septic arthritis of sternoclavicular joint in a healthy patient - Mustfar, Siti Nor Suzeana; Haroon, Raihanah; Abd Aziz, Azian (Springer Nature, 2024)
In an otherwise healthy adult, septic arthritis of the sternoclavicular joint is very uncommon. Usually, individuals with a history of intravenous drug usage or those with impaired immune systems are affected. The usual mode of spread is hematogenous spread or direct spread via neighbouring sources of infection. We report a rare case of mediastinitis and lung empyema preceded by sternoclavicular septic arthritis in an otherwise healthy 49-year-old woman due to Salmonella sp. Radiological imaging showed left sternoclavicular joint collection with bone destruction. The literature only contained reports of two prior occurrences of sternoclavicular joint septic arthritis caused by Salmonella. If diagnosed early, patients usually respond to medical treatment such as aspiration and antibiotics, as was the case with our patient.